Software ventures international strategic plan - Montevirgen, Luisa Diaz (Animo Repository, 2006)
This strategic management paper is for Software Ventures International Corporation (SVI), the authors employer. This paper intends to provide the company with a strategic plan based on its task environment and how the changes in its macroenvironment affect its position in the industry. The company is in the Information Processing industry it addresses the needs of institutional buyers for business solutions that involve processing of data to be used for supporting management decisions. This study is often referred to as the IT-enabled services. These services include information technology services such as systems development, implementation, and maintenance, contact center services, medical transcription, data encoding, content management, animation, among others. SVI has been able to establish itself as one of the well-known local IT companies in the Philippines. In 2000, which was the dawn of the business processing outsourcing (BPO), the company engaged in contact center and business services. As such, the following corporate objectives were defined based on this vision: (1) to increase net profits by at least 25% annually until 2010 and (2) to increase revenue at an annual growth rate not less than 15% annually until 2010. The need for rapid growth that will enable the company to complete and meet the requirements of venture capitalists has been given primary importance in formulating the objectives. These objectives will be attained through the strategies formulated based on the threats, opportunities, strengths, and weakness of the company. The key implements values and broad societal expectations are also taken into consideration in defining the strategies. Frameworks have been used to analyze SVI nature of business and industry and to develop strategies that achieve its objectives. The companys task environment is analyzed and then the threats and opportunities brought about by the effect of potential changes in the macroenvironment on the determinants of the five forces of competitive strategy were identified. Among the threats identifies are as follows: the political instability in the country the increasing trend of outsourcing services, which increases the intensity of rivalry among the players the rapid developments in technology, particularly in information and communications technology (ICT) the very likely emergence of China as the next global outsourcing leader the expected decline in IT investments in the coming years the effect of the United States anti-outsourcing law to the industry and the declining supply of English proficient workers in the country. Changes in the macroenvironment provided the following opportunities: the governments plan to streamline processes through investments in ICT increase in demand for contact center services growing strength of associations dedicated to promoting industry growth availability of capital through venture capitalist who are willing to provide funds in exchange of very appealing returns increasing demand for financial data management services among corporate organizations and the increasing need to focus on core competence and cost-cutting measures that call for outsourcing of non-core activities or even functions. In order to achieve SVIs objectives, the company shall take advantage of the opportunities and find means of coping with the threats, with the strengths and weakness in mind. Thus, the companys strengths and weaknesses were derived based on the previously identified threats and opportunities. What capabilities are available to grab the opportunities and manage the threats? What does SVI lack that hinders it from optimizing the benefits offered by the changes in the business environment? Strengths weaknesses are identified by first analyzing the companys value chain the assets and capabilities that enable the performance of the primary and support activities or the lack thereof. SVI can actually take advantage of the availability of systems that enable it to monitor the efficiency and cost of operations. With its pool of highly skilled and gifted employees, the said systems can be enhanced to provide the functions that will facilitate management in effectively controlling costs. Systems required to support that data processing operations are already in place. Because of the top managements commitment to quality, the company has already been CMM Level 5-and ISO 9001-certified. This only shows that matured processes are already in place. The company also has had experience in developing and implementing a system for the government. This gives it an advantage projects because it has already proven its capability with regard to similar functions. These strengths may enable SVI to take hold of the promising future of the BPO industry. However, it has to overcome its weaknesses to make this possible. The company is currently heavily burdened by debt. This can be attributed to weak cost and financial management. Collection efforts also have to improve in order to allow increased turnover of cash. Employees may be skilled but not enough people actually possess the skills that are in demand today. This calls for retooling of employees. The dynamic nature of the industry requires speedy delivery of services and proofs of concept. SVI is at a disadvantage in this area because product development takes a long time. Organizations that outsource usually demand for a well-developed business continuity plan. With the political instability in the country, this is of primary significance. SVI may have already laid out its policies and procedures regarding this but has not yet cascaded it to middle management. The author analyzed the current strategies of the company and found that most are supposed to be able to achieve the objectives. However, the implementation plan has to be revised and put into action immediately. Each strategic dimension was reviewed to verify whether the current strategies are indeed effective. The top management intends to focus on delivering services to the Philippines government, as well as governments of countries similar to ours. The governments plan to eliminate non-value-adding process through automation presents a great opportunity to outsourcing service providers. Since SVI already has an experience in dealing with and managing projects involving government institutions, this will work to the companys advantage. Targeting the government as the market segment to pursue may present a lot opportunities but also carries with it the burden of being associated with a particular administration and difficult manager. SVI will also continue to deliver service directly to customers. No middlemen will be involved in selling and delivering its service. The company is vertically integrated in way since the Business Service Group obtains its systems and IT services from the software Service Group. Although not directly linked legally with its services from the software Service Group. Although not directly linked legally with its suppliers, it has already formed strategic partnerships with software giants like IBM and Oracle. The following additional corporate strategies are suggested: 1.Invest in the development of employees skills. This should go hand in hand with motivating actions to maintain inventory of the necessary skills. The company shall also invest in developing new technologies and processes. Cost effective processes that may be out-of-the-box can provide a great edge against the competitors. 2.Provide a standard basic application and procedures in providing business services. Since the companys projects involve data encoding/transcription and content management, there should be a modular application available for the basic services. The systems that will be used in operations should be parameterized to allow customization of the application without the need for revision or enhancement of the programs. Standard procedures should also be established to provide a readily available business process model. This will not only save cost as it shortens setup time, but improves perception of the customer on the company as it allows earlier start of production possible. 3.Invest in development and/or enhancement of systems that will optimize efficiency of operations. These systems shall enable the management to monitor and manage operational costs. For the business services, this shall be on a day-to-day basis. 4.Reduce financial leverage to make a better impression on the clients as regards continuity of business operations and to provide the company more chances of obtaining funds for investments. This shall be achieved through debt restricting and obtaining funds from venture capitalists. In order to convince the latter to invest in the company, SVI should promise and deliver high returns. The business plan that will be shown to prospective investors should lay out how the company intends to achieve this. 5.Provide more ancillary that will improve client relations in the long run. This involves post-purchase and post-implementation service that provide convenience to the clients. SVIs competitive advantage used to lie in its ability services at low cost to the customer. However, increasing number of foreign players who have better technology and methodology has made the companys costs relatively higher. Add to this effect of peso appreciation. The companys competitive advantage shall be renewed through investments in assets and capabilities. Details of such decision are based on the analysis obtained using the Wharton model of Competitive Advantage. Functional strategies for marketing, operations, finance, human resources, and information management were developed based on the corporate objectives and the direction to which the company is heading based on the formulated corporate strategies. Marketing aims to increase service revenue by 20% in 2006 and by 25% annually from 2007 up to 2010. This will achieved by focusing marketing efforts on the government. The latter is a huge untapped market that offers a great opportunity for BPO service providers. Service may include IT development and maintenance and performance of processes that are safe to outsource. Despite the managements decision to focus on servicing governments, the company will still continue offering its services to other organizations (i.e corporate and non-profit). To better expose SVI to prospective clients, particularly foreign governments, it shall form strategic alliances with multinational IT firms like IBM and Oracle. Operational objectives include the following: (1) reduction of operating costs by 2% (2) maintaining a 10% increase in most of the variable costs across the five-year period (2006-2010) (3) reduce defect rate to 1% (4) expedite systems implementation period to four months (5) reduce turnaround time for product development to one month and (6) be able to effect changes in capacity in one week. As mentioned earlier, standardizing the basic applications and procedures for the business services will allow cost cutting and reduction of setup time. This will also improve product development time. Expertise in particular business areas will be developed by providing the business analysts with the knowledge and skills necessary to better understand and appreciate certain business processes. Technical skills will be honed by providing trainings on technologies that are mostly to be used in developing systems. Since the companys major weakness lies in its financial position, improving the financial leverage is of utmost concern. Outstanding debt shall be restricted by negotiating with creditors. Funds required for investments and operations shall be obtained through capital infusion from venture capitalist. Since these groups require fairly high yield, SVI has to ensure high profits and attractive cash flows for the next five years. Venture capitalists usually intend to exit from their investment after five years, thus the objective of going public by 2011 was set. Attainment of these objectives and implementation of the said strategies are highly dependent on effective cost management. Objectives for human resources are focused on finding and keeping the valuable employees. These employees have the appropriate skills and attitude that will enable SVI to achieve its goals. To properly align the development of employees with the companys direction, definition of resource requirements will always be based on the corporate strategies. In order to motivate the employees to stay and deliver quality results, they will be offered individual career development plans and shall be offered with an attractive compensation package at par with industry leaders. Competency based appraisal system shall be employed to encourage employees to develop skills require to climb up SVIs corporate ladder. Information management plays a crucial role in attaining the corporate and functional objectives. Top and middle managers are dependent on the information being fed to them when making decisions. Therefore, they shall be provided with the information they need when they need it. To make information processing within the company more efficient, production tools, performance monitoring systems, and financial systems shall be integrated. The last section of this paper illustrates how the strategies are going to be implemented through the 7s and 8-SIT frameworks. A steering committee composed of the top management and representatives of the major functional areas shall be formed to initialize the implementation of the action items. Project teams shall be assigned to handle the development and implementation of policies, procedures, and systems necessary to roll out the strategies. Trainings will also be provided to prepare the employees to handle their respective responsibilities. Team building sessions will be held to form unity within each team and to develop camaraderie. Capital will be made available to support the implementation. The progress of the strategy implementation shall be reviewed by the steering committee on a periodic bais to ensure that results are presented."